PEMBERDAYAAN GEN Z MELALUI EDUKASI TRADING DAN INVESTASI BERJANGKA DI PT. AGRODANA FUTURES SURABAYA - Pramesty, Gadis Dyah; Rini, Hesty Prima (Gapenas Publisher, 2025)
Empowering the younger generation, particularly Gen Z, in the financial sector has become a strategic necessity to foster a financially literate and responsible society. Low financial literacy among youth often leads to engagement in high-risk trading and investment activities without adequate knowledge, resulting in potential financial losses. Through the educational program “Discussion on Responsible Futures Trading and Investment” organized by PT. Agrodana Futures Surabaya, this community service initiative aims to provide a comprehensive understanding of basic futures trading concepts, risk management, and the importance of regulatory compliance in the commodity futures trading (PBK) industry. The program implementation involved lectures, interactive discussions, case studies on illegal investments, and trading simulations using MetaTrader 4 demo accounts. Evaluation results indicated a significant increase in participants’ understanding of key concepts such as margin, leverage, stop loss, and the importance of choosing legally registered brokers under Bappebti regulations. This educational effort contributes to empowering Gen Z to become critical, risk-aware investors who are not easily swayed by unrealistic profit promises. Moreover, the program builds a bridge between academic institutions and the financial industry to enhance national financial literacy and promote sustainable financial behavior among youth.